Examining the impact of environmental and socio-economic factors in countries with high and low child mortality: the role of electricity, healthcare, and industrialization - Salma Akter; Liton Chandra Voumik; Md. Shaddam Hossain; Miguel Angel Esquivias; Dulal Chandra Pattak (Discover Sustainability)
Abstract This study explores the relationships between electricity consumption, healthcare spending, carbon dioxide (CO2) emissions, GDP growth, industrialization, urbanization, fertility rates, and child mortality rates in ten countries with the highest and lowest child mortality rates, using Driscoll-Kraay’s standard error approach (DKSE). The DKSE regression results show that in countries with high child mortality, the mortality declines significantly with electricity access, health expenditures, urbanization, and GDP growth, and increases with CO2 emissions and fertility rates. In countries with low child mortality rates, the mortality declines significantly with health expenditures, GDP, and urbanization, and rises with industrialization. Electricity access, CO2 emissions, and fertility rates do not impact child mortality in these countries. The study emphasizes the importance of electricity access, health expenditures, GDP, and tailored urbanization and industrialization strategies in child welfare and the need for comprehensive global policies.